FORMULATION OF ECONAZOLE NITRATE AS A TOPICAL SOLUTION - HAMZA SAMIN, LAITH (Iraqi Journal of Pharmaceutical Sciences, 2017)
Econazole nitrate (EN) is considered as the most effective agent for the treatment of all forms ofdermatomycosis caused by dermatophytes. This study was carried out to formulate a stableEconazole nitrate solution for a topical use through preparation of different formulas and selectedthe most suitable one. The results indicated that the use of propylene glycol and ethanol as a vehiclefor EN which is very slightly soluble in water gave amore stable formula as EN topical solution,with a shelf life of about 3.15 years .The data also indicated that the light accelerated thedegradation of EN, while the type of container (glass or plastic) had no effect on the rate of drug.The overall results of this study suggest that the selected formula could be used as a topical solutionfor EN.